Eleven year performance of an Integrated Counseling and Testing Center in a tertiary care hospital in Himachal Pradesh, India - Sunite A Ganju; Suruchi Bhagra; Anil K Kanga; Dig V Singh; Raman Chauhan (Wolters Kluwer Medknow Publications, 2014)
Introduction: The integrated counseling and testing centre (ICTC) has proved to be an essential human immunodeficiency virus (HIV) infection prevention intervention, especially in nations where poverty, social inequality, and weak health infrastructure exist. Objectives : The study was conducted to (i) assess the performance of ICTC in a referral hospital over a period of 11 years (ii) understand the regional risk determinants of HIV-positive clients. Materials and Methods : In this record based hospital study, data from January 2000 to December 2010 of all ICTC attendees and HIV-positive clients (excluding pregnant women; surveillance in this group is being conducted routinely) was collected by reviewing the records, compiled, and analyzed. Results : A total of 19,234 clients were counseled, of which 17,411 were tested and 970 were detected positive for HIV. The HIV seropositivity amongst the total tested clients was 5.57%. The intake of clients attending ICTC consistently increased from 781 clients in 2000 to 5574 clients in 2010. Amongst the total 970 HIV positives the ratio between male and female positives was 3:2 (m = 584; f = 386). Of these, 42.1% were in the age group of 25-44 years and children (<15 years) accounted for 7.8%. The heterosexual route of transmission was documented in 77.4%. In 13.6% (n = 132) HIV-positive clients, the route of transmission was not identified. The provider initiated client visits increased significantly from 4.85% in 2006 to 82.05% in 2010 than the direct walk-in clients (P < 0.0000001). However, the HIV-positive clients were three times more in the direct walk-in clients than in the provider initiated clients (P < 0. 0000001). Conclusion : Increased utilization of ICTC reflects the overall attitudinal changes in behavior and heterosexual high risk behavior continues to be the major route of HIV transmission.